Increase grit and learning satisfaction in physical education among student-athletes: augmented reality Learning is the Solution? - Sandey Tantra Paramitha; Edi Setiawan; Irfan Benizar Lesmana; Amayra Tannoubi; Arumugam Raman; Ahmet Kurtoğlu; Novri Gazali; Taupik Rochman; Samson Getu; Joseph Lobo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to investigate the effect of using augmented reality (AR) on increasing the level of grit and learning satisfaction among student-athletes. We adopted mixed-methods sequential explanatory design. A total of 40 student-athletes, participants were allocated into control group (CG, n = 20), and experiment group (AR, n = 20). The results of quantitative research based on the Paired sample t-test show that there are significant pre- and post-test differences in CG (p < 0.050, and AR (p < 0.05) in grit and satisfaction. At the same time, the results of 2-Way ANOVA show that there is an effect of time on the variables grit (CoI [p < .001, η²p = 0.810], PoE [p < .001, η²p = 0.837] and satisfaction (TaI [p < .001 , η²p = 0.812], PT [p < .001, η²p = 0.726], TP [p < .001, η²p = 0.649 ], IP [p < .001, η²p = 0.796], there is a group effect on the grit variable (CoI [p < .001, η²p = 0.488], PoE [p < .001, η²p = 0.451] and satisfaction (TaI [p = 0.025, η²p = 0.126], PT [p = 0.011, η²p = 0.159], IP [ p = 0.048, η²p = 0.099], but not found in the TP variable (p = 0.079, η²p = 0.079), and there was an interaction between grit (CoI [p < .001, η²p = 0.707], PoE [p < .001, η²p = 0.718], and satisfaction (TaI [p = 0.031, η²p = 0.117], but there was no interaction on PT [p = 0.113, η²p = 0.065 ], TP [p = 0.638, η²p = 0.006], IP [p = 0.565, η²p = 0.009]. While qualitative findings showed that student-athletes argued that AR has an advantage to create an interactive, interesting, and easy to use learning program to learn various skills in sports.